Knowledge sharing in a multicultural environment: challenges and opportunities - Luyanda Dube; Patrick Ngulube (South African Journal of Libraries and Information Science, 2012)
The article underscores the process of knowledge sharing in a multicultural organisational environment. Generally, multiculturalism emanates from being influenced by different contexts that provide the potential for human diversity. It results in disparate behavioural patterns and bodies of knowledge which lead to variance in terms of racial, sexual, age and cultural orientations. The process of sharing knowledge is complex and is susceptible to multicultural variances. Considering that knowledge sharing processes and probable multicultural influences are contextual, the purpose of the article is to establish the extent of knowledge flows in the Department of Information Science at the University of South Africa. In particular the article seeks to give an overall view on how knowledge is shared across intergenerational, cultural and interracial lines in the Department. The qualitative approach was considered appropriate for this study because it focuses on observing events from the perspectives of those who are involved and is aimed at understanding the attitude, behaviour and opinions of those individuals (Powell & Connaway 2004). A basic interpretive qualitative research design was used for this study. Data was collected through interviews and document analysis. The data were inductively analysed and the findings are presented and discussed using references to the literature that informed the study.